Comparison of Predictive Immunohistochemical Marker Expression of Primary Breast Cancer and Paired Distant Metastasis using Surgical Material: A Practice-Based Study. (April 2016) - Kulka, Janina; Székely, Borbála; Lukács, Lilla V.; Kiss, Orsolya; Tőkés, Anna-Mária; Vincze, Eszter; Turányi, Eszter; Fillinger, János; Hanzély, Zoltán; Arató, Gabriella; Szendrői, Miklós; Győrffy, Balázs; et al.
Parallel studies of primary breast carcinomas and corresponding distant metastases samples reveal considerable differences. Our aim was to highlight this issue from another perspective and provide further data based on 98 patient samples: 69 primary breast carcinoma and 85 distant metastases from bone, central nervous system (CNS) and lung (56 paired). Two independent series of immunohistochemical reactions with different antibodies for estrogen receptor (ER), progesterone receptor (PgR) and human epidermal growth factor receptor 2 (Her2), along with HER2 fluroscence in situ hybridization (FISH) were performed on tissue microarrays to classify breast carcinoma and distant metastases samples into Luminal A, Luminal B-proliferating, Luminal B-HER2+, HER2+ and triple negative (TNBC) surrogate breast cancer groups. Correlation and agreement between the two assessments of ER and PgR were fair-to-moderate, and almost perfect for HER2 and Ki67. There was 40% discordance concerning immunophenotype between breast carcinomas and distant metastases. Most common metastatic site of ER+ breast carcinoma was the skeletal system (59.2%), whereas that of TNBCs was the CNS (58.8%) and lungs (23.5%). Distant metastases in bones were mostly luminal (54.3%), in the CNS, Luminal B (53.2%), and in the lung, TNBC (37.5%). The change of drugable properties of primary breast cancers in the respective bone and CNS metastases suggests that characterization of the metastasis is necessary for appropriate treatment planning.